Relationship between Magnetic Resonance Imaging and Interictal 99mtc-Hmpao Spect Findings in Epilepsy Patients with Focal EEG Abnormalities (Annals of Medical Research, 2021)
None
Keywords: Epilepsy; Electroencephalography; Single Photon Emission Computed Tomography; Magnetic Resonance İmaging.